Structure of Zinc Coating on Steels Formed by Diffusion Saturation in Nitrogen-Containing Atmosphere - Petrova Larisa (EDP Sciences, 2021)
Diffusion technique of metallization is applied for receiving of zinc coatings on low-carbon steel with transitional zone. Structure of diffusion zinc layers after saturation of 09Mn2Si steel in ammonia at different temperatures is examined. Effects on saturation temperature on thickness of diffusion layers are discovered. Process at 600⁰C forms diffusion layers with high strengthening level and with smooth microhardness profiles. Elements (Fe, Zn, N) spectrums are analyzed, and phase composition of zinc coating and of transitional zone is determined.